A prognostic analysis of patients with acute leukemia and a history of central nervous system involvement undergoing umbilical cord blood transplantation - Zichang Shen; Bingbing Yan; Xinyue Zhang; Yue Wu; Xiaoyu Zhu (Blood Science)
To investigate the efficacy and prognosis of umbilical cord blood transplantation (UCBT) in patients with acute leukemia (AL) and a history of central nervous system leukemia (CNSL). We retrospectively evaluated 62 patients with AL and a history of CNSL who underwent UCBT at our center between January 2015 and December 2022 (CNSL-positive group). From a concurrent cohort (n = 777) without a history of CNSL, propensity score matching at a 1:2 ratio was conducted based on age, sex, and diagnosis to select 124 matched controls (CNSL-negative group). The results revealed a significantly higher 4-year cumulative incidence of relapse (28.8% vs 16.8%, p = 0.038) and central nervous system (CNS) relapse after UCBT (14.7% vs 3.7%, p = 0.004) in the CNSL-positive group than in the CNSL-negative group. Furthermore, the 4-year leukemia-free survival (42.0% vs 66.2%, p = 0.004) and overall survival (49.6% vs 69.9%, p = 0.009) rates in the CNSL-positive group were significantly lower than those in the CNSL-negative group. Fine–Gray proportional hazard regression multivariate analysis identified pretransplant CNSL history as an independent high-risk factor for CNS relapse after UCBT (hazard ratio [HR] = 5.710, 95% confidence interval [CI] = 1.737–18.770, p = 0.004). These findings underscore the need to optimize conditioning regimens and graft-vs-host disease prophylaxis and explore novel prophylactic strategies for UCBT to improve long-term survival in patients with AL and a history of CNS involvement.